Youth Empowerment in Prevention of Drug Abuse in Muara Badak Ulu Village, Muara Badak District, Kutai Kartanegara Regency, East Kalimantan Province - Trisna Waty Riza Eryani; Putri Anwar (Jurnal Pengabdian Masyarakat Bestari, 2023)
This drug problem is very troubling among teenagers. Where more and more teenagers are involved in drug abuse. Adolescence is a very appropriate target to be used as a strong foundation in preventing the increasingly widespread drug abuse. The aim of this service is to empower teenagers in preventing drug abuse in Muara Badak Ulu Village, Muara Badak District, Kutai Kartanegara Regency. The method used is through lectures and discussions. The results of community service activities for 10 teenagers in Muara Badak Ulu Village, Muara Badak District, are that it is hoped that teenagers can fortify themselves with faith and positive activities so that they can avoid drug abuse and become a successful and happy generation in the future.